Disaster Commercialism and Disaster Capitalism - Mark Petticrew (HealthcarePapers, 2022)
The pandemic has exposed vulnerabilities in public health. Those vulnerabilities have been exploited by commercial actors, and the harmful effects – for example, increases in obesity, alcohol harms and inequalities – are being seen. The pandemic, like other public health crises, has been a rich feeding ground for disaster capitalism, which sees crises as a further opportunity to undermine the role of government and to replace the state with corporate structures that support pro-corporate interests and undermine the public’s health. Public health crises urgently need to be freed from the shackles of vested interests and policy satisficing.
Keywords: commercial determinants of health, capitalism, public health, inequalities, feeding ground, disaster capitalism